Patients’ view on gene therapy development for lysosomal storage disorders: a qualitative study - Eline C. B. Eskes; Cathrien R. L. Beishuizen; Eleonore M. Corazolla; Tessa van Middelaar; Marion M. M. G. Brands; Hanka Dekker; Erica van de Mheen; Mirjam Langeveld; Carla E. M. Hollak; Barbara Sjouke (Orphanet Journal of Rare Diseases, 2022)
Abstract Introduction Several new treatment modalities are being developed for lysosomal storage disorders (LSDs), including gene therapy. As the currently available treatment options and their influence on disease progression differ greatly within the spectrum of LSDs, willingness to undergo gene therapy might vary among patients with LSDs and/or their representatives. The width of the LSD spectrum is illustrated by the differences between type 1 Gaucher disease, Fabry disease and Mucopolysaccharidosis type III (MPS III). For type 1 Gaucher and Fabry disease several therapies are available, resulting in a near normal or improved, but individually varying, prognosis. No treatment options are available for MPS III. Aim To identify factors influencing patients’ and/or their representatives’ decisions regarding undergoing gene therapy. Methods Focus group discussions and semi-structured interviews were conducted with patients with type 1 Gaucher disease, Fabry disease and MPS III. Parents of MPS III patients were included as patients’ representatives. Results Nine Gaucher patients, 23 Fabry patients, two adult MPS III patients and five parents of MPS III patients participated in the study. The five main themes that arose were: outcome of gene therapy, risks and side effects, burden of gene therapy treatment, current situation and ethical aspects. Participants’ views ranged from hesitance to eagerness to undergo gene therapy, which seemed to be mostly related to disease severity and currently available treatment options. Severe disease, limited treatment options and limited effectiveness of current treatment augmented the willingness to choose gene therapy. Gaucher and Fabry patients deemed the burden of treatment important. Fabry and MPS III patients and parents considered outcome important, suggesting hope for improvement. When asked to rank the factors discussed in the focus group discussions, Gaucher patients ranked outcome low, which could indicate a more cautious attitude towards gene therapy. Conclusion This study underlines the importance of exploring patients’ needs and expectations before using limited resources in the development of therapies for patient groups of which a significant subset may not be willing to undergo that specific therapy.